Analisis Faktor Eksternal dan Internal Sebagai Dasar Strategi Pengembangan UMKM Kebab Sultan Panyileukan - Nur Fauziah Putri; M Raihan Ramadhani; Annisa Pratiwi Sundari; Satria Adi Putra; Fadlillah Ramadhan; Siti Mardiana (PENG: Jurnal Ekonomi dan Manajemen, 2025)
This study aims to analyze internal and external factors that affect the sustainability of the Kebab Sultan MSME business in Panyileukan, and to develop appropriate development strategies based on these conditions. The research method used is descriptive qualitative with data collection techniques through semi-structured interviews with MSME owners and employees. Data analysis was carried out using the SWOT (Strengths, Weaknesses, Opportunities, Threats) approach to identify the strengths, weaknesses, opportunities, and threats faced by the Kebab Sultan MSME. The results of the study show that MSMEs have several strengths such as distinctive product tastes and strategic locations, but also face weaknesses in terms of marketing management. From the external side, the opportunities are wide open with the increasing public interest in fast food, but there are threats from similar business competition around the Panyileukan area. Based on the results of the SWOT analysis, development strategies that can be applied include increasing digital promotion, increasing brand awareness, and more efficient operational management. This research is expected to be the basis for strategic considerations for MSME actors in developing their businesses sustainably.